Multi-sector Collaboration: Success Stories of Tourism Village Development - rohim rohim; Asmuni Asmuni; M. Zaenul Muttaqin (Program Pascasarjana Universitas Negeri Makassar, 2021)
Village-Owned Enterprises (BUMDES) are one of the business entities mandated by law as the spearhead of driving the economy in the village. This study wants to know the extent of the BUMDES collaboration strategy with other parties in building and developing tourist villages and other business units. This study uses qualitative research methods, with interviews with several trusted sources in Bhinor Village, Paiton District, Probolinggo Regency. This study shows the success of the BUMDES collaboration strategy with other parties. There are three BUMDES collaboration strategies in developing BUMDes, namely first, collaboration with PT. PJB UP Paiton in optimizing CSR to develop the quality of human resources and infrastructure for tourist villages and BUMDES business units. Second, cooperation with community groups in exploring village potential and recruiting workers. Third, Collaborating with Micro, Small and Medium Enterprises (MSMEs) to develop and promote local products. In short, BUMDES has succeeded in optimizing collaborative collaboration with other parties in driving the economy in the village. In addition, this study uses analysis of Strengths, Weaknesses, Opportunities and Threats (SWOT) as an effort to face competition with competitors.